Food and health in early modern Europe : diet, medicine and society, 1450-1800 - Gentilcore, David (Bloomsbury Academic, an imprint of Bloomsbury Publishing Plc., 2016)
"Food and Health in Early Modern Europe is both a history of food practices and a history of the medical discourse about that food. It is also an exploration of the interaction between the two: the relationship between evolving foodways and shifting medical advice on what to eat in order to stay healthy. It provides the first in-depth study of printed dietary advice covering the entire early modern period, from the late-15th century to the early-19th; it is also the first to trace the history of European foodways as seen through the prism of this advice. David Gentilcore offers a doctor's-eye view of changing food and dietary fashions: from Portugal to Poland, from Scotland to Sicily, not forgetting the expanding European populations of the New World. In addition to exploring European regimens throughout the period, works of materia medica, botany, agronomy and horticulture are considered, as well as a range of other printed sources, such as travel accounts, cookery books and literary works. The book also includes 30 illustrations, maps and extensive chapter bibliographies with web links included to further aid study. Food and Health in Early Modern Europe is the essential introduction to the relationship between food, health and medicine for history students and scholars alike."--Bloomsbury Publishing.